Inoculation with Azospirillum brasilense or Bacillus spp. improves root growth and nutritional quality of araucaria (Araucaria angustifolia) seedlings - Kondo, Yanka Rocha; da Cruz, Sonia Purin; Chanway, Christopher; Kaschuk, Glaciela (Forest ecology and management, 2024)
Araucaria angustifolia is a conifer endemic to southern South America that is threatened with extinction, necessitating strategies to enhance its reforestation success. We assessed the effects of inoculation with plant growth-promoting bacteria (PGPB) on araucaria seedlings to determine whether PGPB increases their quality. The experiment was carried on in a three-way factorial scheme and an additional control, with six replications. A volume of 50 mL of diluted inoculant (Azospirillum brasilense Abv5 + Abv6 or Bacillus subtilis BRM2084 + B. megaterium (renamed Prestia megaterium) BRM119) was applied at planting (to seeds or to the substrate) or at through irrigation after seedling emergence, at concentrations of 0.2 %, 0.4 %, 0.8 %, or 1.6 % (v/v, inoculant/water). Destructive sampling was conducted (1) when seedlings only had the stem, (2) when the first branch was formed, and (3) when the second branch was established. The inoculants increased taproot growth and shoot P and N contents at the stem phase, but not later stages. Improved seedling mass, nutrient content and Dickson Quality Index were associated to inoculation with A. brasilense in the substrate and through irrigation. The most promising inoculant concentration was 0.9 %. Thus, inoculation with PGPB increases araucaria seedlings quality, which could be beneficial for seedling establishment in the field and should be further explored as a restoration strategy. •Plant growth-promoting bacteria increased araucaria seedling quality.•Inoculants for annual crops may be suitable for forest species.•Inoculants may be applied directly to substrate or through irrigation.